(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The starting point of this paper is the plurality and the diversity of the theoretical platforms of non-classical logics, which is one of the dominant caracteristic of contemporary logical investigations. In that way, the unity of the paradigm ofthe classical logic is being undermined and its epistemologically priviledged status is being seriously questioned. In this paper, the author is treating two main questions: first, the question of the sources of this plurality, that is, the motives which inspire the need of building alternatives to the classical logic, and second - the question of the epistemological and methodological implications brought about by the existence of many consistent, complete and independent alternative systems. The variations in the conceptualisation of the truth and the consequence vis-a-vis the classical conception are being treated as main generators of theoretical and practical differences between non-classical systems.